Life Cycle Assessment of solid oxide fuel cell systems for data centers A comparative study between three fuel alternatives: natural gas, biogas, and hydrogen - Teixeira Taboada, Sabela (My University, 2022)
The aim of this thesis was to evaluate the environmental performance of the solid oxide fuel cell (SOFC) BlueGEN BG-15 manufactured by Solid Power. To conduct this study, an attributional Life Cycle Assessment (LCA) was conducted to compare three fuel alternatives to be fed into the SOFC. This thesis was conducted in collaboration with RISE ICE and it is part of two European Union projects that deal with using fuel cells to provide reliable prime power for data centers. The research question to be answered was: “What is the environmental performance of a SOFC run with three different fuels: biogas from food waste, natural gas and hydrogen?”. To answer this question, the system was studied from cradle-to-grave using data provided from the manufacturers as well as literature. Biogas is locally produced from food waste in Sweden, natural gas comes from imports to Italy and the hydrogen is manufactured by electrolysis using electricity from the Italian energy grid. The different processes were modelled in the LCA software SimaPro. The database used was EcoInvent 3.7 and Environmental Footprint 3.0 was the impact method selected. The environmental impacts were evaluated for climate change, particulate matter, acidification, water scarcity, fossil fuels resource use and minerals and metals resources use. A contribution analysis to check the possesses with the highest environmental burden was done. Also, a sensitivity analysis was conducted to evaluate how the impacts change when renewable energy is used to produce the hydrogen. Results revealed that fuel production is responsible for most of the impacts. Only mineral and metals resource use is mostly affected by manufacturing the SOFC. Comparing the three fuel alternatives, hydrogen has by far the highest environmental impact. Biogas has the lowest climate change impact and fossil fuel resource use. For the remaining categories biogas and natural gas impact is similar. The environmental impact from hydrogen depends on the production pathways considered and could become an environmental competing alternative if renewable energy is used to produce it. This way, climate change impact would be reduced. However, other impacts linked to each energy source may arise. The thesis concluded with some mitigation measurements as well as possible areas of improvement for future research on this area.
Keywords: SOFC, LCA, sustainability, biogas, natural gas, hydrogen, energy, renewable energy, data center, electricity, power, fuel cell.